Seed Layer-Assisted Growth of Bi2s3 Nanorod Films for Efficient Photoelectrochemical Water Splitting - Radhalayam, D (Elsevier Ltd, 2025)
Nanocrystalline Bi2S3 thin films show significant potential for efficient photoelectrochemical (PEC) water splitting applications. However, traditional chemical bath deposition (CBD) methods face challenges such as poor adhesion, limited thickness, and the need for multiple depositions. This study addresses these issues by introducing a seed layer-assisted growth method, utilizing Sb2S3 as the seed layer to enhance the synthesis of uniform and strongly adherent Bi2S3 nanorod films on FTO-coated glass substrates. Three types of Bi2S3 films were prepared: pristine Bi2S3, Bi2S3 on an Sb2S3 seed layer, and Bi2S3 with the addition of SbCl3 to the starting solution. The pristine Bi2S3 films formed nanorods 50–100 nm in length, with a direct bandgap of 1.25 eV, and a photocurrent density of 4.6 mA/cm2 at 1 V vs Ag/AgCl. The Bi2S3 films deposited on an Sb2S3 seed layer exhibited improved nanorod density and size (100–150 nm) and an increased photocurrent of 10.0 mA/cm2 at 1 V vs Ag/AgCl. Conversely, the addition of SbCl3 to the starting solution resulted in smaller nanorods (50–100 nm), a higher energy gap of 1.32 eV, and a reduced photocurrent density of 7.0 mA/cm2. These findings demonstrate that the use of an Sb2S3 seed layer prior to Bi2S3 growth significantly enhances the nanorod density and improves both the physical and PEC properties of the films, making this method a promising approach for developing more efficient PEC water-splitting devices. This seed layer approach provides a pathway for the large-scale development of various semiconductor thin films for photoelectrochemical and other optoelectronic device applications. © 2024